STRATEGIC AREAS OF MODERNIZATION OF THE HIGHER EDUCATION MANAGEMENT SYSTEM IN UKRAINE (Economic journal of Lesya Ukrainka Volyn National University, 2019)
Introduction. One of the essential components of the education system is higher education. As Ukrainian higher education institutions operate in the dynamically developing European Higher Education Area (EHEA), there is a need to implement strategic measures for the modernization of higher education. The purpose of the article is to analyze comparatively the transformation of the measures of modernization of educational management declared by the state since 2002 and their implementation according to the Law of Ukraine «On Higher Education». Results. This study compares measures to modernize education management in the National doctrine of educational development and the National strategy for the development of education in Ukraine for the period up to 2021, as well as the constituent parts of the Law of Ukraine «On Higher Education», where they are implemented. The realization of the main priorities of the EHEA in the legislative acts of Ukraine is considered. Conclusions. It is determined, that the number of educational management modernization measures in the National education development doctrine is almost twice the number of educational management modernization measures in the National education development strategy. The doctrine envisaged a transition to programmatic and targeted management; introduction of a new ethics of management activity based on the principles of mutual respect, positive motivation; broader involvement in the management of talented youth, women, and nurturing leaders in education. The strategy pointed to the development of a system of measures (scientific, methodological, financial and economic, etc.) regarding the implementation of the idea of autonomy of educational institutions, the extension of their rights and opportunities for financial independence. The main priorities of the EHEA are stated in the following legislative acts of Ukraine: the Law «On Higher Education», the Order of the Ministry of Education and Science of Ukraine «Some Issues of Recognition of Foreign Documents on Education in Ukraine», CMU Resolution «On Approval of the Regulations on the Procedure for Exercising the Right to Academic Mobility».
Keywords: modernization measures, education management system, higher education, regulations, European Higher Education Area